Glass composite clarifying agent and preparation method of glass
By using a glass composite clarifier composed of Yuanming powder, Na2SiF6, NaCl, CeO2 and ZnO in the melting process of aluminosilicate glass, the problem of difficulty in eliminating bubbles is solved, and better clarification effect and glass quality are achieved.
Patent Information
- Application Number
- CN202411513637.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-11
AI Technical Summary
During the melting process of aluminosilicate glass, bubbles are difficult to eliminate, resulting in poor clarification effect, affecting the optical uniformity, transmittance and mechanical strength of the glass.
A glass composite clarification agent is used, which consists of Yuanming powder, Na2SiF6, NaCl, CeO2 and ZnO. Through the synergistic effect of these components, the viscosity of the glass liquid is reduced, gas release is promoted, and bubble number is reduced.
It effectively improves the clarification effect of glass, reduces the number of bubbles, increases the transmittance and mechanical strength of glass, and enhances the quality of glass.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass manufacturing, and in particular to a glass composite clarifier and a method for preparing glass. Background Art
[0002] With the booming development of portable mobile phone communications, the development of 5G communications has brought about major changes in the entire mobile phone accessories industry, especially the development and changes of mobile phone covers. Traditional mobile phone covers are mainly made of metal materials, but the wave absorption performance of metal materials is generally poor, which has a shielding effect on mobile phone signals and cannot meet the requirements of 5G communications. At the same time, consumers have higher and higher requirements for the appearance and texture of mobile phone back panels. Glass stands out in this trend due to its good wave absorption performance, unique appearance and good texture. However, traditional glass is brittle and prone to microcracks, making its actual mechanical strength 2-3 orders of magnitude lower than the theoretical mechanical strength. Compared with traditional glass materials, aluminosilicate glass has the advantages of good light transmittance, high scratch resistance, low hardness, easy surface treatment, richer colors, etc., and has great market potential.
[0003] During the production process of float aluminosilicate glass, a large amount of gas will be generated in the melting stage. Since the aluminum content in the raw materials exceeds 12%, the melting temperature of the raw materials increases, resulting in a large viscosity of the system during the melting process, making it difficult to release the gas, making clarification very difficult. Due to the presence of bubbles, the finished glass has extremely poor optical uniformity, transmittance, mechanical strength and other properties. Therefore, a clarifier needs to be added during the glass production process to eliminate bubbles in the glass production process. In the traditional production process, a single clarifier is usually used, such as sodium sulfate, sodium sulfate, etc. According to different clarification principles, the current single clarifiers mainly include redox clarifiers, high-temperature cracking type, volatile clarifiers, etc. However, for high-aluminum glass with a high aluminum content, the effect of a single clarifier is relatively limited, and it is impossible to completely discharge the bubbles in the glass, and even it is impossible to produce qualified glass. Therefore, composite clarifiers have great development prospects in the current production process of aluminosilicate glass. Summary of the invention
[0004] The object of the present invention is to provide a glass composite clarifier and a method for preparing glass, so as to solve the problem that bubbles are difficult to eliminate during the melting process of aluminosilicate glass, resulting in poor clarification effect.
[0005] In order to achieve the above object, the first aspect of the present invention provides a glass composite clarifier, which comprises the following components in parts by weight: 10-50 parts of sodium sulfate, 1-25 parts of Na2SiF6, 5-40 parts of NaCl, 5-35 parts of CeO2, and 5-35 parts of ZnO; The particle size of the alum is 30-80 μm, the particle size of Na2SiF6 is 50-100 μm, the particle size of NaCl is 15-80 μm, the particle size of CeO2 is 160-200 nm, and the particle size of ZnO is 20-60 nm.
[0006] Optionally, the glass composite clarifier comprises the following components in parts by weight: 20-40 parts of glauber salt, 5-20 parts of Na2SiF6, 10-35 parts of NaCl, 10-30 parts of CeO2, and 10-30 parts of ZnO.
[0007] Optionally, the particle size of the alum is 40-60 μm, the particle size of Na2SiF6 is 60-90 μm, the particle size of NaCl is 30-60 μm, the particle size of CeO2 is 170-190 nm, and the particle size of ZnO is 30-50 nm.
[0008] Optionally, the mass ratio of NaCl, CeO2 and Na2SiF6 is 1:(0.4-2):(0.2-1.5).
[0009] Optionally, the glass composite clarifier makes the surface stress of the glass>820MPa and the stress layer depth>102μm.
[0010] A second aspect of the present invention provides a method for preparing glass, the method comprising: After the glass raw material mixture is uniformly mixed with the glass composite clarifier provided by the first aspect of the present invention, the mixture is placed in a platinum crucible and heated to a first temperature for melting, and then heated to a second temperature for clarification and homogenization to obtain glass liquid; The glass liquid is subjected to molding, annealing and cooling treatment to obtain a glass product.
[0011] Optionally, the glass composite clarifier accounts for 0.1-0.8% of the total weight of the glass raw material and the glass composite clarifier.
[0012] Optionally, the glass composite clarifier accounts for 0.3-0.6% of the total weight of the glass raw material and the glass composite clarifier.
[0013] Optionally, the glass raw material includes the following components in parts by weight: 59-68 parts of SiO2, 10-16 parts of Al2O3, 8-12 parts of LiO2, 0-7 parts of Na2O, 30-5 parts of B2O, 50-6 parts of P2O, 0-2 parts of ZrO2, and 0-0.1 parts of SnO2.
[0014] Optionally, the first temperature is 1600-1700° C., the holding time is 300-420 min, the second temperature is 1650-1750° C., the holding time is 30-60 min; the annealing temperature is 500-700° C., the time is 10-30 min.
[0015] Through the above technical scheme, the glass composite clarifier of the present invention is composed of five single-component clarifiers. The composite clarifier can give full play to the synergistic effect of each component, reduce the viscosity of the glass liquid, effectively promote the release of gas during the glass melting process, reduce the number of bubbles, improve the clarification effect, and achieve continuous clarification; at the same time, it can increase the surface stress of the glass and the depth of the stress layer, and enhance the quality of the glass.
[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0018] The first aspect of the present invention provides a glass composite clarifier, which comprises the following components in parts by weight: 10-50 parts of glauber salt, 1-25 parts of Na2SiF6, 5-40 parts of NaCl, 5-35 parts of CeO2, and 5-35 parts of ZnO; the particle size of the glauber salt is 30-80μm, the particle size of Na2SiF6 is 50-100μm, the particle size of NaCl is 15-80μm, the particle size of CeO2 is 160-200nm, and the particle size of ZnO is 20-60nm.
[0019] The glass composite clarifier of the present invention is composed of five single-component clarifiers. The composite clarifier can give full play to the synergistic effect of each component, reduce the viscosity of the glass liquid, effectively promote the release of gas in the glass melting process, reduce the number of bubbles, improve the clarification effect, and achieve continuous clarification; at the same time, it can increase the surface stress of the glass and the depth of the stress layer, and enhance the quality of the glass.
[0020] According to the present invention, optionally, the glass composite clarifier comprises the following components in parts by weight: 20-40 parts of sodium sulfate, 5-20 parts of Na2SiF6, 10-35 parts of NaCl, 10-30 parts of CeO2, and 10-30 parts of ZnO. The glass composite clarifier of the present invention uses the above components to promote the escape of bubbles in the glass liquid to varying degrees, so that the glass liquid can continuously discharge bubbles of different sizes in different temperature ranges, and complete the clarification process through the synergistic effect of the components, thereby obtaining glass with fewer bubbles, higher transmittance and better mechanical properties.
[0021] According to the present invention, optionally, the particle size of the glauber salt is 40-60 μm, the particle size of Na2SiF6 is 60-90 μm, the particle size of NaCl is 30-60 μm, the particle size of CeO2 is 170-190 nm, and the particle size of ZnO is 30-50 nm. The particle sizes of the components of the present invention are different, and the specific surface areas are also different. The different specific surface areas produce a difference in sedimentation velocity, so that it produces a step-by-step clarification effect in the isothermal melt, further exerts the synergistic effect of each component, greatly improves the clarification effect, and thus also improves the quality of the prepared glass.
[0022] According to the present invention, optionally, the mass ratio of NaCl, CeO2 and Na2SiF6 is 1:(0.4-2):(0.2-1.5). Through the above embodiment, a better clarification effect can be obtained.
[0023] According to the present invention, optionally, the glass composite clarifier makes the surface stress of the glass>820MPa and the stress layer depth>102μm, and the glass has higher surface stress and stress layer depth.
[0024] A second aspect of the present invention provides a method for preparing glass, the method comprising: After the glass raw material mixture is uniformly mixed with the glass composite clarifier provided by the first aspect of the present invention, the mixture is placed in a platinum crucible and heated to a first temperature for melting, and then heated to a second temperature for clarification and homogenization to obtain glass liquid; The glass liquid is subjected to molding, annealing and cooling treatment to obtain a glass product.
[0025] The present invention adds a composite clarifier to the glass, the number of bubbles in the glass liquid increases greatly, the bubble size rapidly increases, which is conducive to the overflow of bubbles, the glass clarification effect is good, and thus the quality of the prepared glass is improved. In addition, the addition of the glass composite clarifier will not release toxic and harmful gases, is more environmentally friendly, and has little erosion on the refractory material of the glass melting furnace, which can improve the service life of the furnace and reduce production costs.
[0026] According to the present invention, optionally, the glass composite clarifier accounts for 0.1-0.8% of the total weight of the glass raw material and the glass composite clarifier.
[0027] According to the present invention, optionally, the glass composite clarifier accounts for 0.3-0.6% of the total weight of the glass raw material and the glass composite clarifier. The glass composite clarifier of the present invention can achieve a good clarification effect with a small amount when used, has good clarification efficiency, and will not affect the quality of the formed glass.
[0028] According to the present invention, optionally, the glass raw material includes the following components in parts by weight: 59-68 parts of SiO2, 10-16 parts of Al2O3, 8-12 parts of LiO2, 0-7 parts of Na2O, 30-5 parts of B2O, 50-6 parts of P2O, 0-2 parts of ZrO2, and 0-0.1 parts of SnO2.
[0029] According to the present invention, optionally, the first temperature is 1600-1700°C, the holding time is 300-420min, the second temperature is 1650-1750°C, the holding time is 30-60min; the annealing temperature is 500-700°C, the time is 10-30min.
[0030] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0031] Example 1 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.35% of the total weight of the glass raw materials and the glass composite clarifier, including 27 parts of sodium chloride, 23 parts of sodium sulfate, 10 parts of zinc oxide, 20 parts of cerium oxide, and 20 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0032] Example 2 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace and heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C and keep them warm for 40 minutes to clarify and homogenize, and obtain glass liquid; the content of the glass composite clarifier is 0.38% of the total weight of the glass raw materials and the glass composite clarifier, including 30 parts of sodium chloride, 30 parts of sodium sulfate, 13 parts of zinc oxide, 12 parts of cerium oxide, and 15 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0033] Example 3 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.42% of the total weight of the glass raw materials and the glass composite clarifier, including 25 parts of sodium chloride, 40 parts of sodium sulfate, 15 parts of zinc oxide, 15 parts of cerium oxide, and 5 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×15mm.
[0034] Example 4 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.46% of the total weight of the glass raw materials and the glass composite clarifier, including 35 parts of sodium chloride, 20 parts of sodium sulfate, 10 parts of zinc oxide, 17 parts of cerium oxide, and 18 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0035] Example 5 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.5% of the total weight of the glass raw materials and the glass composite clarifier, including 12 parts of sodium chloride, 30 parts of sodium sulfate, 30 parts of zinc oxide, 15 parts of cerium oxide, and 13 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0036] Example 6 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.53% of the total weight of the glass raw materials and the glass composite clarifier, including 15 parts of sodium chloride, 27 parts of sodium sulfate, 13 parts of zinc oxide, 30 parts of cerium oxide, and 15 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0037] Example 7 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.57% of the total weight of the glass raw materials and the glass composite clarifier, including 30 parts of sodium chloride, 20 parts of sodium sulfate, 15 parts of zinc oxide, 15 parts of cerium oxide, and 20 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0038] Example 8 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 1; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.4% of the total weight of the glass raw materials and the glass composite clarifier, including 25 parts of sodium chloride, 30 parts of sodium sulfate, 20 parts of zinc oxide, 10 parts of cerium oxide, and 15 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0039] Comparative Example 1 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 2; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass composite clarifier is 0.3% of the total weight of the glass raw materials and the glass composite clarifier, including 48 parts of sodium chloride, 8 parts of sodium sulfate, 2 parts of zinc oxide, 40 parts of cerium oxide, and 2 parts of sodium fluorosilicate; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0040] Comparative Example 2 S1: Weigh the glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 2; after mixing the glass raw materials, mix them evenly with the glass composite clarifier, place them in a platinum crucible, send them into a high-temperature lifting furnace and heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C and keep them warm for 40 minutes to clarify and homogenize, and obtain glass liquid; the content of the glass composite clarifier is 0.6% of the total weight of the glass raw materials and the glass composite clarifier, including 20 parts of sodium chloride, 45 parts of sodium sulfate, and 35 parts of cerium oxide; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0041] Comparative Example 3 S1: Weigh glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 2; after mixing the glass raw materials, mix them evenly with the glass clarifier sodium chloride, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass clarifier is 0.6% of the total weight of the glass raw materials and the glass clarifier, of which sodium chloride is 100 parts; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0042] Comparative Example 4 S1: Weigh glass raw materials according to the ratio, and the glass raw materials and their ratios are shown in Table 2; after mixing the glass raw materials, mix them evenly with the glass clarifier cerium oxide, place them in a platinum crucible, send them into a high-temperature lifting furnace, heat them to 1650°C for melting for 350 minutes, and then heat them to 1660°C for 40 minutes for clarification and homogenization to obtain glass liquid; the content of the glass clarifier is 0.6% of the total weight of the glass raw materials and the glass clarifier, of which cerium oxide is 100 parts; S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0043] Comparative Example 5 S1: Weigh glass raw materials according to the ratio. The glass raw materials and their ratios are shown in Table 2. After mixing the glass raw materials, place them in a platinum crucible and send them into a high-temperature lifting furnace to heat to 1650°C for melting for 350 minutes, and then heat to 1660°C for 40 minutes to clarify and homogenize to obtain glass liquid. S2: pouring the glass liquid into a mold preheated to 500°C for molding, annealing at 570°C for 20 minutes, and then cooling to obtain a glass product; S3: The glass products are processed by wire cutting, CNC engraving, processing, cleaning, edge grinding and drying to obtain block glass of 15mm×15mm×5mm.
[0044] Test Examples 1-8 and Comparative Examples 1-5 The physical properties of the glasses prepared in Examples 1-8 and Comparative Examples 1-5 were measured, and the results are shown in Tables 1 and 2.
[0045] The number of bubbles per cubic millimeter was recorded by optical microscope observation.
[0046] The surface stress and stress layer depth were tested using the FSM-6000LE surface stress meter produced by Orihara Industries, Ltd., Japan.
[0047] Table 1.
[0048]
[0049] Table 2.
[0050]
[0051] It can be seen from Table 1 and Table 2 that the composite clarifier provided by the present invention has a better clarification effect than single-component sodium chloride or cerium oxide, and also has a better clarification effect than conventional composite clarifier components of sodium chloride, cerium oxide and glauber salt.
[0052] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0053] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0054] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A glass composite clarifier, characterized in that: The glass composite clarifier comprises the following components in parts by weight: 10-50 parts of sodium sulfate, 1-25 parts of Na2SiF6, 5-40 parts of NaCl, 5-35 parts of CeO2, and 5-35 parts of ZnO; The particle size of the alum is 30-80 μm, the particle size of Na2SiF6 is 50-100 μm, the particle size of NaCl is 15-80 μm, the particle size of CeO2 is 160-200 nm, and the particle size of ZnO is 20-60 nm.
2. The glass composite clarifier according to claim 1, wherein: The glass composite clarifier comprises the following components in parts by weight: 20-40 parts of sodium sulfate, 5-20 parts of Na2SiF6, 10-35 parts of NaCl, 10-30 parts of CeO2 and 10-30 parts of ZnO.
3. The glass composite clarifier according to claim 1, wherein: Preferably, the particle size of the alum is 40-60 μm, the particle size of Na2SiF6 is 60-90 μm, the particle size of NaCl is 30-60 μm, the particle size of CeO2 is 170-190 nm, and the particle size of ZnO is 30-50 nm.
4. The glass composite clarifier according to claim 1, wherein: The mass ratio of NaCl, CeO2 and Na2SiF6 is 1:(0.4-2):(0.2-1.5).
5. The glass composite clarifier according to claim 1, wherein: The glass composite clarifier makes the surface stress of the glass greater than 820 MPa and the depth of the stress layer greater than 102 μm.
6. A method for preparing glass, characterized in that: The method includes: After uniformly mixing the glass raw material mixture and the glass composite clarifier according to any one of claims 1 to 5, placing the mixture in a platinum crucible and heating it to a first temperature for melting, and then heating it to a second temperature for clarification and homogenization to obtain glass liquid; The glass liquid is subjected to molding, annealing and cooling treatment to obtain a glass product.
7. The method according to claim 6, wherein: The glass composite clarifier accounts for 0.1-0.8% of the total weight of the glass raw material and the glass composite clarifier.
8. The method according to claim 7, wherein: The glass composite clarifier accounts for 0.3-0.6% of the total weight of the glass raw material and the glass composite clarifier.
9. The method according to claim 6, wherein: The glass raw material comprises the following components in parts by weight: 59-68 parts of SiO2, 10-16 parts of Al2O3, 8-12 parts of LiO2, 0-7 parts of Na2O, 0-5 parts of B2O3, 0-6 parts of P2O5, 0-2 parts of ZrO2, and 0-0.1 parts of SnO2.
10. The method according to claim 6, wherein: The first temperature is 1600-1700°C, and the holding time is 300-420 minutes; the second temperature is 1650-1750°C, and the holding time is 30-60 minutes; The annealing temperature is 500-700° C., and the annealing time is 10-30 minutes.